Cotidiano de trabajo y formación de educadores sociales: la relación con educandos en centros educativos asistenciales - Pinheiro, Leandro R. (Cuadernos de Trabajo Social, 2007)
In Porto Alegre (Brazil), public education supported by the welfare system, in most cases, plays its role in very poor neighborhoods. The population of these communities, especially children and adolescents, has strong references in the work of social educators, not only pedagogical, but affective and socio-symbolic references, in its daily practice. As such, this report presents the results of research with educators who coordinate a welfare system-supported educational center in the community of Lomba do Pinheiro: The Child and Adolescent Support Center (CPCA). Examining the question «How does the formal education of the educators influence the educational practice implemented with the students?», the work has been taken from an action research perspective supported by observation techniques, relationship mapping and interviews, with the goal being to know the life histories of the people involved, to characterize the work context built within the organization and, from that point, to reflect on the relationships established with the students. The inferences thus derived point out that educators, on the one hand, establish relationships strongly guided by «the protection» of the students and, on the other hand, stimulate practices which are hardly emancipatory in nature and are quite hierarchal relative to the community where they perform their work. In this work, the research was oriented to question the pedagogical references of the educators, as practices derived from their self-eco-organization, to stimulate them to establish new socio-educational relationships with the objective of creating (self) shaping activities in the work of educating.